Nuclear reactions - McCarthy, I. E. (Ian Ellery), 1930-2005 (Commonwealth and international library. Selected readings in physics., 1970)
Nuclear Reactions deals with the mechanisms of nuclear reactions and covers topics ranging from quantum mechanics and the compound nucleus to the optical model, nuclear structure and nuclear forces, and direct interactions. The structure of the atomic nucleus and capture of slow neutrons are also discussed, along with nuclear reactions at high energies, neutron capture and nuclear constitution, and elastic and inelastic diffraction scattering. This book is comprised of 17 chapters and begins with an overview of early successes and difficulties experienced by nuclear physics as a discipline, pa.